PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI MELALUI MEDIA GAMBAR PADA SISWA KELAS XI IPB SMA KATOLIK VILLANOVA MANOKWARI - Kamisopa, Merlin; Warami, Hugo; Baru, Yosefina (JURNAL TRITON PENDIDIKAN, 2017)
The research focuses on students’ writing competency of descriptive paragraph through picture media. Two research questions guiding this research are (1) can writing competency of descriptive paragraph be improved through picture media? (2) how is the degree of writing competency of descriptive paragraph measured through picture media?. The method used in this research is Classroom Action Research through four implementation stages, namely: (a) planning, (b) action, (c) observation, (d) reflection. Data analysis used in this research are: (1) quantitatif data analysis through testing, and (2) qualitatif data analysis through (a) observation and (b) documentation.Thus, at the cicle stage, students having the completency of 0,00% increased at the cicle stage I to become 80,95% and at the cicle stage II, the number slightly decreased to 71,43%. The creased number was affected by the number of students absent from the class. The final writing process of descriptive paragraph through picture media at the first cicle stage was 9,52%. This changes at the cicle I stage that became 85,71% and at the cicle II stage decreased to 76,19%. The research shows that the writing competency of descriptive paragraph through picture media for grade XI IPB at Villanova Chatolic High School Manokwari increases.